Health checks for autistic adults: study protocol for a cluster randomised controlled trial - Jeremy R. Parr; Helen Taylor; Colin Wilson; Clare Scarlett; Sarah Al-Asmori; Carole Buckley; Sally-Ann Cooper; Cristina Fernandez-Garcia; Tracy Finch; Rhianna Lees; Nicholas Lennox; Hannah Merrick; et al. (Trials)
Abstract Background Autistic people commonly have physical and mental health conditions. They also frequently experience barriers to accessing healthcare, contributing to problems identifying and treating health conditions. These factors may lead to increased and earlier morbidity and lower average life expectancy for autistic people. Health checks specifically designed for autistic people, incorporating adjustments to healthcare, may help to overcome these barriers and reduce health inequalities. This trial aims to investigate the clinical and cost-effectiveness of a primary care health check for autistic adults and explore factors related to implementation such as acceptability and feasibility of delivery. The trial is co-designed and delivered by health professionals, autistic people, carers and supporters, and researchers. Methods This is a clinical and cost-effectiveness, cluster randomised controlled trial of a primary care health check for autistic adults. Primary care practices will be randomised into one of two groups (intervention or control). Two hundred autistic adults (aged 18 years and over) who provide baseline data will be recruited via participating practices. Data will be collected through quantitative and qualitative methods. The primary outcome will be the incidence of new health needs/conditions detected and met at 9 months (data gathered from participant’s GP records). Secondary outcomes will include the following: cost-effectiveness, measured as incremental cost per quality-adjusted life year gained over 9 months; the extent of health monitoring and health promotion needs met at 9 months; the incidence of social care needs identified at 9 months; changes in participant or carer general health; changes in quality of life; primary and secondary health and social care resource usage and costs. A qualitative study will explore views about the acceptability of the health check, its utility and future use. Discussion This study will examine the effectiveness and cost-effectiveness of a primary care health check for autistic adults in identifying new health conditions and needs. If the intervention is effective, it would provide strong evidence for implementation into routine healthcare, therefore enabling earlier health condition diagnosis and opportunities for treatment, reducing the health inequalities experienced by autistic people. Trial registration ISRCTN, retrospectively registered on 20 July 2023. https://www.isrctn.com/ISRCTN30156776 (ISRCTN registration number: 30156776).